Electric Vehicle Tourism in Queensland - Kaiying, Wu; Lin, Yushi; Luo, Luyao; Liu, Qing; Jia, Zemin; Zhang, Ruihao; Tan, Xi; Langham, Jo’Anne (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
This study reviews four government programs of electric vehicle (EV) tourism and three industry practices globally, to determine the potential of EV tourism in Queensland. Recommendations for government includes focusing on related policy supports and public-private partnerships to development EV tourism. For tourism business, customer-centric approach to service development and related marketing will improve EV adoption in tourism.